On the Politics of Ugliness (Springer International Publishing, 2018)
Ugliness or unsightliness is much more than a quality or property of an individual's appearance-it has long functioned as a social category that demarcates access to social, cultural, and political spaces and capital. The editors of and authors in this collection harness intersectional and interdisciplinary approaches in order to examine ugliness as a political category that is deployed to uphold established notions of worth and entitlement. On the Politics of Ugliness identifies and challenges the harmful effects that labels and feelings of ugliness have on individuals and the socio-political order. It explores ugliness in relation to the intersectional processes of racialization, colonization and settler colonialism, gender-making, ableism, heteronormativity, and fatphobia. On the Politics of Ugliness asks that we fight against visual injustice and imagine new ways of seeing.